2015
DOI: 10.1148/radiol.2015141950
|View full text |Cite
|
Sign up to set email alerts
|

Elbow US: Anatomy, Variants, and Scanning Technique

Abstract: As with other musculoskeletal joints, elbow ultrasonography (US) depends on the examination technique. Deep knowledge of the relevant anatomy, such as the bone surface anatomy, tendon orientation, nerves, and vessels, is crucial for diagnosis. It is important to be aware of the primary imaging pitfalls related to US technique (anisotropy) in the evaluation of deep tendons such as the distal biceps and peripheral nerves. In this article, US scanning technique for the elbow as well as the related anatomy, primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
54
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 38 publications
0
54
0
Order By: Relevance
“…The MCL can be evaluated on a supine patient with the shoulder in abduction and external rotation and the elbow at 90°. 24 Dynamic US can demonstrate the medial joint instability when a valgus stress is applied; however, this examination may not be diagnostic owing to expected joint widening in the dominant arm of throwing athletes. 9 The LCL complex can be evaluated with the hand in supination as a varus stress is applied; however, there is no consensus about the role of US in evaluation of the LCL.…”
Section: Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…The MCL can be evaluated on a supine patient with the shoulder in abduction and external rotation and the elbow at 90°. 24 Dynamic US can demonstrate the medial joint instability when a valgus stress is applied; however, this examination may not be diagnostic owing to expected joint widening in the dominant arm of throwing athletes. 9 The LCL complex can be evaluated with the hand in supination as a varus stress is applied; however, there is no consensus about the role of US in evaluation of the LCL.…”
Section: Testingmentioning
confidence: 99%
“…9 The LCL complex can be evaluated with the hand in supination as a varus stress is applied; however, there is no consensus about the role of US in evaluation of the LCL. 24 …”
Section: Testingmentioning
confidence: 99%
“…Images in 2 planes are obtained on anterior, lateral, medial, and posterior joint surfaces, with particularly attention to the site of maximal pain or swelling. The elbow is extended to obtain images of the joint anteriorly, and flexed to obtain other views [9]. Comparison with the unaffected extremity may help to identify abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…Using ultrasound to evaluate musculoskeletal and joint pain in patients with underlying bleeding disorders may have particular value. In hemophiliacs, clinical examination of a painful joint is unreliable, which may prompt clinicians to perform unnecessary invasive procedures or provide costly empiric factor replacement [9-11]. Recent studies have demonstrated the limitations of clinical examination for the detection of joint effusion in hemophiliacs with suspected hemarthrosis, with improved diagnostic accuracy using point-of-care ultrasound [8,11].…”
Section: Discussionmentioning
confidence: 99%
“…The pronator teres, located at the anteromedial side of the elbow and proximal forearm, is composed of a humeral head and an ulnar head (Figure ) . The deep, smaller ulnar head originates from the medial border of the coronoid process and the medial side of the brachialis tendon.…”
Section: Anatomy and Biomechanicsmentioning
confidence: 99%